Transient Astrophysics with the Square Kilometre Array - Fender, R.; Stewart, A.; Macquart, Jean-Pierre; Donnarumma, I.; Murphy, T.; Deller, A.; Paragi, Z.; Chatterjee, S. (2015)
This chapter provides an overview of the possibilities for transient and variable-source astrophysics with the Square Kilometre Array. While subsequent chapters focus on the astrophysics of individual events, we focus on the broader picture, and how to maximise the science coming from the telescope. The SKA as currently designed will be a fantastic and ground-breaking facility for radio transient studies, but the scientifc yield will be dramatically increased by the addition of (i) near-real-time commensal searches of data streams for events, and (ii) on occasion, rapid robotic response to Target-of-Opprtunity style triggers.